Perbandingan Learning Management System Edmodo dan Moodle Dalam Pembelajaran Online - Endang Retnoningsih (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2017)
Abstrak: E-learning adalah proses belajar yang difasilitasi dan didukung melalui pemanfaatan Teknologi Informasi dan Komunikasi. E-learning dapat mengakomodasi sistem pembelajaran yang mengatur peran pengajar, siswa, pemanfaatan sumber belajar, pengelolaan pembelajaran, sistem evaluasi dan monitoring pembelajaran. Suatu sistem pengelolaan pembelajaran online terintegrasi yaitu Learning Management System (LMS). Dengan Edmodo akan lebih mudah memonitor interkasi siswa dalam Edmodo Learning Environtment. Edmodo dirancang untuk membuat siswa bersemangat belajar dilingkungan yang lebih akrab. Moodle adalah sebuah program aplikasi yang dapat merubah sebuah media pembelajaran kedalam bentuk web. Aplikasi ini memungkinkan siswa untuk masuk kedalam "ruang kelas" digital untuk mengakses materi-materi pembelajaran. Edmodo dan Moodle merupakan pilihan yang sangat tepat untuk digunakan sebagai media pembelajaran online karena terdapat banyak fitur-fitur yang ditawarkan dalam hal mengoptimalkan pembelajaran juga mempermudah kegiatan belajar mengajar antara pengajar dan siswa. Kata kunci: edmodo, e-learning, learning management system, moodle Abstract: E-learning is a learning process that is facilitated and supported through the utilization of Information and Communication Technology. E-learning can accommodate learning systems that regulate the roles of teachers, students, use of learning resources, learning management, evaluation systems and monitoring of learning. Learning Management System (LMS). With Edmodo it will be easier to monitor student interactions in Edmodo Learning Environtment. Edmodo is designed to make students eager to learn in a more familiar environment. Moodle is an application program that can transform a learning medium in web form. This application allows students to enter digital "classroom" to access learning materials. Edmodo and Moodle is an excellent choice to use as an online learning medium because there are many features offered in terms of optimizing learning as well as teaching and learning activities between teachers and students. Keywords: edmodo,e-learning, learning management system, moodle